Dimensions and estimated mechanical characteristics of the humerus after long-term tennis loading - Haapasalo, H.; Sievanen, H.; Kannus, P.; Heinonen, A.; Oja, P.; Vuori, I. (Journal of Bone and Mineral Research, 1996)
This study evaluated the effects of long-term unilateral physical activity (tennis) on the playing arm humerus. Total lengths of both humeri, site-specific widths, and the bone mineral contents (BMC) at the proximal, middle, and distal parts of the bones were measured using dual-energy X-ray absorptiometry (DXA). Bone mineral apparent density (BMAD), cortical wall thickness (CWT), cross-sectional moment of inertia (CSMI), and section modulus (Z) were approximated from the DXA data for describing the bone's mechanical characteristics more concretely. The study population consisted of 67 healthy, competitive tennis players (17 young men with a mean age [+/- SD] of 25 +/- 5 years, 30 young women with a mean age of 19 +/- 3 years, and 20 older women with a mean age of 43 +/- 5 years) and 57 sedentary controls (16 young men with mean age of 25 +/- 5 years, 25 years, 25 young women with a mean age of 21 +/- 3 years, and 16 older women with mean age of 39 +/- 6 years). All the players had competitive playing histories greater than 4 years. The young male and female players had started their playing careers in childhood (men at the age of 10 +/- 3 years, women 9 +/- 2 years), while the older female players started the training at adulthood (29 +/- 6 years). The playing-to-nonplaying or dominant-to-nondominant arm differences in humeral length ranged from +0.2 to +1.4%, the difference being significant in young male players (+1.4%), young female controls (+1.1%), and older female players (+0.7%). When comparing players' relative side-to-side length differences with those of the controls, no significant differences were found. Significant side-to-side differences in humeral width were observed in all groups except male controls. Compared with the controls, the relative side-to-side width differences were significantly larger at the proximal humerus of the young male players (controls +1.2%, players +3.7%) and the distal humerus of young female players (controls -0.2%, players +1.6%). Compared with the controls, the players' relative side-to-side differences in BMC (range, +7.6 to +25.2%), BMD (+5.8 to +22.5%), BMAD (+5.5 to +20.4%), CWT (+6.9 to +45.2%), CSMI (+7.8 to +26.4%), and Z (+3.0 to +21.7%) were significantly larger in all measured humeral sites except BMAD in the distal humeri of the older female players. These relative ide-to-side differences were clearly and significantly larger in the young players (+11.7 to +45.2%) than in the older players (+3.0 to +12.4%). In conclusion, long-term intensive tennis playing, especially if started in childhood or adolescence, clearly increases the humeral BMC, BMD, and CWT but seems to have only a minor effect on the width of this particular bone. In this respect, there seems to be no sex difference. However, along with the increases in mineral mass and density, the changes in bone width are important in increasing the bending stiffness and strength of the humerus. In older players, the relative side-to-side differences are at the same level or only slightly larger than those in their age-matched controls. This suggests that even intense physical loading of a mature bone is only marginally better in increasing the bone mass, bone density, and CWT of the target bone than the normal daily use of the dominant extremity.